Solar superstorm of AD 774 recorded subannually by Arctic tree rings - J. Uusitalo (Nature Portfolio, 2018)
Tree rings retain information of sudden variations of ancient radiocarbon (14C) content, however the origin and exact timing of these events often remain uncertain. Here, the authors analyze a set of Arctic tree rings and link a rapid increase in 14C to a solar event that occurred during the spring of AD 774.